Ferroelectrics: Revealing the Effects of Trace Oxygen Vacancies on Improper Ferroelectric Manganite with In Situ Biasing (Adv. Electron. Mater. 4/2019). (9th April 2019) - Cheng, Shaobo; Meng, Qingping; Han, Myung‐Geun; Deng, Shiqing; Li, Xing; Zhang, Qinghua; Tan, Guotai; Botton, Gianluigi A.; Zhu, Yimei
Abstract : In article number1800827, Shaobo Cheng, Yimei Zhu and the co‐workers report a novel ferroelectric switching dynamic behavior in the single‐phase multiferroic material YMnO3 . In situ observations and corresponding numerical calculations demonstrate that defect chemistry plays an important role in domain switching and can be utilized as an additional parameter for controlling the electricfield distribution within multiferroic materials.